ENTREPRENEURSHIP AS AN ECONOMIC FORCE ON RURAL DEVELOPMENT IN ANAMBRA STATE, NIGERIA - OKEKE,M. N.,; ONUORAH, A. N.,; NEBOLISA, O. T.,; OBOREH,J. C., (IJRDO - Journal of Business Management, 2019)
This study examined entrepreneurship as an economic force in the development of rural areas of Anambra state. Specifically, the study investigated the influence of poor access to finance, unemployment, entrepreneurship orientation and infrastructural facilities on rural development. Relevant literature conceptual, theoretical and empirical literatures were reviewed. The theoretical framework was anchored on opportunity-based entrepreneurship theory, resource-based entrepreneurship theory and the human capital entrepreneurship theory. Survey research design was adopted in this study. The population of the study comprised1350selected registered entrepreneurs in Anambra state. Taro Yamane’s formula was applied for determination of a sample size of 309. The tools used in analysing the data collected were simple percentages, descriptive statistics and correlation analysis and the study also employed Multiple Regression Analysis (MRA) in testing the hypotheses. Findings revealed that access to finance, unemployment and entrepreneurship orientation had significant influence on rural development while infrastructural facilities had no significant effect on rural development. The study therefore, concluded that entrepreneurship as an economic force had a significant influence on rural development in Anambra. It was recommended that government should initiate policies to create access to finance to entrepreneurs. Unemployment problem should not be left in the hands of government alone rather government should employ the public private partnership approach so as to allow the involvement of private individuals in helping to establish entrepreneurial development centres as well. Entrepreneurship orientation should be made an element at all levels of learning primary, secondary and tertiary institutions. Good infrastructure generally promotes business activities regardless of the size or type of enterprise.